Engaging interaction and long-term engagement with WhatsApp in an everyday life context: exploratory study. Issue 4 (12th January 2021) - Martinez-Comeche, Juan-Antonio; Ruthven, Ian
Abstract : Purpose: The aim of this exploratory study is to analyze if the most used factors related to the engaging interaction and long-term engagement with online applications can be applied to WhatsApp in a context of everyday life in Madrid and to investigate what parameters would best describe the engagement with WhatsApp in this context. Design/methodology/approach: A qualitative method was employed to explore the cognitive, emotional and behavioral factors that mainly comprise the experience of a user with an online application, both at a point in time and over time. Data from 30 semi-structured interviews and questionnaires from six group chats were collected and analyzed. The sample was made up of people aged from 13 to 58 years old. Findings: Findings suggest that the factors used in this study to evaluate long-term engagement and engaging interactions with WhatsApp are relevant, except for cognitive factors related to engaging interactions, indicating that the cognitive point of view is more difficult to apply in the engaging interaction analysis. Other attributes related to information retrieval are suggested, best suited to the informative use of this tool. Originality/value: Long-term engagement studies are scarcer concerning Mobile Instant Messaging applications. Regarding engagement interaction, its analysis focusing on WhatsApp has not been approached. This study suggests the convenience of using parameters related to information to evaluate the engaging interaction, according to the informative use of the application.